2016
DOI: 10.3389/fnbeh.2015.00361
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training at a Young Age Attenuates Deficits in the zQ175 Mouse Model of HD

Abstract: Huntington's Disease (HD) is a progressive neurodegenerative disorder that causes motor, cognitive, and psychiatric symptoms. In these experiments, we tested if operant training at an early age affected adult cognitive deficits in the zQ175 KI Het (zQ175) mouse model of HD. In Experiment 1 we trained zQ175 mice in a fixed-ratio/progressive ratio (FR/PR) task to assay learning and motivational deficits. We found pronounced deficits in response rates and task engagement in naïve adult zQ175 mice (32–33 weeks age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…In sum, this experiment indicates that RB5 acts as cognitive enhancer in females trained in a striatal-dependent procedural learning task and rescued procedural learning deficits in zQ175 HD mice. These data are in accordance with previous evidence showing that early experiences of environmental enrichment with cognitive testing not only ameliorated the severity of cognitive deficits in zQ175 mice but this beneficial effect was mostly evident in female mice 29 . At present, the sex difference is not fully understood and will require further investigation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In sum, this experiment indicates that RB5 acts as cognitive enhancer in females trained in a striatal-dependent procedural learning task and rescued procedural learning deficits in zQ175 HD mice. These data are in accordance with previous evidence showing that early experiences of environmental enrichment with cognitive testing not only ameliorated the severity of cognitive deficits in zQ175 mice but this beneficial effect was mostly evident in female mice 29 . At present, the sex difference is not fully understood and will require further investigation.…”
Section: Resultssupporting
confidence: 93%
“…The observation that nuclear ERK modulation ameliorates cognitive deficits in HD models as well as in WT animals suggests an interesting hypothesis. It has been previously shown in a number of HD models, including HdhQ111 and zQ175, that behavioural training or environmental enrichment (EE) can lead to a significant delay in cognitive decline 29,4143 . Interestingly, these effects in HD mouse models have been shown to be gender biased, with females better responding to the treatment, and were paralleled by the alleviation of depression-like behaviour normally more pronounced in females than in males 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The EEG disturbances observed in the Het mice suggest HD pathology, but the link to phenoconversion remains unclear. Previous work has demonstrated that Het mice develop behavioral symptoms, and reason for the lack of apparent symptoms in this particular study is unknown (13, 15, 23). Further research is needed to establish a closer linkage between the symptoms and qEEG biomarkers in the zQ175 Het model.…”
Section: Resultsmentioning
confidence: 72%
“…The behavioural relevance of these forms of plasticity is not well characterized, although they may play a role in cognitive and behavioural flexibility (Cui et al, ; Augustin and Lovinger, ). Disruption of cognitive flexibility is prominent in HD (Lawrence et al, ; Curtin et al, ) and further study of eCB‐mediated plasticity may improve our understanding of these symptoms.…”
Section: Endocannabinoidsmentioning
confidence: 99%
“…The behavioural relevance of these forms of plasticity is not well characterized, although they may play a role in cognitive and behavioural flexibility (Cui et al, 2015;. Disruption of cognitive flexibility is prominent in HD (Lawrence et al, 1996;Curtin et al, 2016) and further study of eCB-mediated plasticity may improve our understanding of these symptoms. eCBs and the HD phenotype Loss of CB1 in HD patients begins at early stages of the disease (Glass et al, 2000;Laere et al, 2010) and occurs on both SPNs and interneurons (Horne et al, 2013).…”
Section: Endocannabinoidsmentioning
confidence: 99%